Partisipasi Pemilih Pemula Dalam Menentukan Pilihan Politik Pada Pemilihan Kepala Daerah Maluku Utara - Wance, Marno; Suhu, Bakri La (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2019)
This study aims to find out the participation of first-time voters in determining political choices and to find out the behavior of first-time voters in determining the candidates for regional elections in North Maluku. This study uses descriptive qualitative which is can as a series of procedures used in solving problems investigated / examined by describing the state of the objects of research at time based on existing facts. Data sources used are primary data and secondary data, Data collection done through observation, interviews and documents analysis.Based on the findings of the study, the level of political participation of first-time voters in determining their political choices in North Maluku regional head elections can be described; the voters are rational enough in deciding their political choices, because the indicators for chosing candidates are based on figures the and datas and the products of political issues sold by the candidatsin their qeetion programs. In addition it also turns out that the first time voters still use an emotional approach with the candidates in channeling voting rights in the elections.This study aims to find out the participation of first-time voters in determining political choices and to find out the behavior of first-time voters in determining the candidates for regional elections in North Maluku. This study uses descriptive qualitative which is can as a series of procedures used in solving problems investigated / examined by describing the state of the objects of research at time based on existing facts. Data sources used are primary data and secondary data, Data collection done through observation, interviews and documents analysis.Based on the findings of the study, the level of political participation of first-time voters in determining their political choices in North Maluku regional head elections can be described; the voters are rational enough in deciding their political choices, because the indicators for chosing candidates are based on figures the and datas and the products of political issues sold by the candidatsin their qeetion programs. In addition it also turns out that the first time voters still use an emotional approach with the candidates in channeling voting rights in the elections.